The modulatory role of second language proficiency on performance monitoring: evidence from a saccadic countermanding task in high and low proficient bilinguals - Singh, Niharika; Mishra, Ramesh K. (Frontiers in Psychology, 2015)
We compared Hindi-English bilinguals differing in their L2 fluency on a saccadic countermanding task which taps inhibitory control as well as monitoring. We particularly explored whether response inhibition and performance monitoring within the oculomotor domain are affected by language proficiency in bilinguals. There were two different oculomotor redirect tasks: Visually Guided Redirect (VGR) task (Experiment1) and Memory Guided Redirect (MGR) task (Experiment 2). In this task typically a target is presented to which subject must make saccade (No step trials), unless a new target appears on the other location after some delay from the first target onset (Step trials). On such trials participants are required to inhibit and cancel the saccade to the first instead program a saccade to the new target. Using trial switch reaction time (TSRT), which is the time taken to inhibit the initiated saccade to the first target, as a measure of response inhibition, and post-stop slowing as a measure of performance monitoring, we observed two important results. It was found that high proficiency bilinguals showed more post-stop slowing on the no-step trials as compared to the low proficiency bilinguals for both VGR and MGR. Secondly, high and low proficiency bilingual exhibited comparable TSRT in both VGR and MGR, showing no altering effect of language proficiency on the response inhibition in bilinguals. These results suggest that bilingualism impacts performance monitoring which is modulated by language proficiency if not the inhibitory control system. Higher fluency may lead to superior cognitive flexibility, and ability to adjust behaviour that facilitates attainment of cognitive goal. These findings are in consonance with other current studies that suggest a top-down effect of bilingualism on action control systems.